Effect of fire intensity on the earlier post-fire succession in Pinus nigra Arnold stands of Taşköprü, Kastamonu - Yılmaz, Fatma Nur; Küçük, Ömer; Güney, Kerim; Sağlam, Bülent (Ormancilik Arastirma Dergisi, 2025)
This study investigates the post-fire vegetation development in black pine (Pinus nigra) stands, which are widely distributed in Kastamonu and are under threat from forest fires. To this end, sampling was conducted in 2017 in the Taşköprü and Bayam Forest Management Directorates, where fires occurred in 2003 and 2012. Sample plots (25 × 50 m) were established using the minimum area method in two regions affected by surface fires (low intensity) and crown fires (high intensity). To observe the temporal effects of high-intensity fire, a sample area from a 2003 fire site was also analyzed and compared using the Shannon diversity index and the Chi-square test. Results showed significant differences in the family Pinaceae and the life form cryptophyte. Although black pine was observed to remain the dominant species after the surface fire, one- and two-year-old species belonging to the Rosaceae and Fabaceae families were recorded during the early stage of vegetation. In areas with reduced canopy closure, species such as Cistus laurifolius, C. creticus, and Rubus sp. were observed. Species composition in the crown fire site closely resembled that of surface fire areas with broken canopy. Cistus laurifolius was the dominant species in crown fire areas, and the highest species diversity was found in the 2003 crown fire site.